2019
DOI: 10.2147/cmar.s191199
|View full text |Cite
|
Sign up to set email alerts
|

<p>Assessment of potential predictive value of peripheral blood inflammatory indexes in 26 cases with soft tissue sarcoma treated by pazopanib: a retrospective study</p>

Abstract: Purpose The aim of this study was to evaluate the prognostic and predictive value of neutrophil-to-lymphocyte ratio (NLR), derived neutrophil-to-lymphocyte ratio (DNLR), lymphocyte-to-monocyte ratio (LMR), and platelet-to-lymphocyte ratio (PLR) in soft tissue sarcoma (STS) cases treated with pazopanib. Materials and methods The study population included 26 STS cases treated with pazopanib for at least 3 months. NLR, DNLR, LMR, and PLR were evaluated at baseline, and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The study included two different cohorts (formerly named typical and malignant SFT) and reported an outcome in PFS, OS, and ORR according to Choi criteria, clearly better than historical control achievement with chemotherapy. Similar to our results, high pretreatment and/or increased NLR values have been previously reported as predictive factors for a shorter PFS and OS in other types of STS treated with pazopanib, such as undifferentiated pleomorphic sarcoma and leiomyosarcoma [ 11 , 12 ]. Likewise, the prognostic role of NLR before treatment has been confirmed in different solid tumours [ 13 ], including STS [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The study included two different cohorts (formerly named typical and malignant SFT) and reported an outcome in PFS, OS, and ORR according to Choi criteria, clearly better than historical control achievement with chemotherapy. Similar to our results, high pretreatment and/or increased NLR values have been previously reported as predictive factors for a shorter PFS and OS in other types of STS treated with pazopanib, such as undifferentiated pleomorphic sarcoma and leiomyosarcoma [ 11 , 12 ]. Likewise, the prognostic role of NLR before treatment has been confirmed in different solid tumours [ 13 ], including STS [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition to tumour cells, neutrophils, macrophages, and lymphocytes infiltrated into the tumour microenvironment can contribute to amplifying inflammatory signalling through cytokines and chemokines. Neutrophils and macrophages secrete tumour-growth-promoting factors, including VEGF, HGF, IL-6, IL-8, MMPs, and elastases [ 12 , 27 ]. Our analysis of gene expression profiles in the tumour microenvironment identified genes implicated in inflammation or immune response, such as PTGS2 and TYK2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soft tissue sarcoma (STS) is a relatively rare malignant tumor that originates from mesenchymal tissue with a heterogeneous category comprised of more than 50 histologic subtypes. 1 , 2 It accounts for approximately 24,000 new cases annually in China and the incidence is higher in adolescents. 3 , 4 The most common histologic subtypes of STS are undifferentiated sarcoma (US), liposarcoma (LPS), synovial sarcoma (SS) and leiomyosarcoma (LMS), which are associated with different molecular characteristics and behavior features.…”
Section: Introductionmentioning
confidence: 99%
“…CBC parameters have been widely investigated as potential prognostic markers for several malignancies in humans, and the role of NLR in predicting survival for STS patients is well established 7,24‐28 . MacFarlane and colleagues found that NLR was significantly higher in dogs with STS compared with dogs with benign soft tissue tumours, although neither NLR nor leukocyte counts correlated with tumour grade in the STS group 11 .…”
Section: Discussionmentioning
confidence: 99%